2015
DOI: 10.3109/02699052.2015.1005135
|View full text |Cite
|
Sign up to set email alerts
|

Self-awareness and traumatic brain injury outcome

Abstract: Primary Objective Impaired self-awareness following a traumatic brain injury (TBI) can reduce the effectiveness of rehabilitation, resulting in poorer outcomes. However, little is understood about how the multi-dimensional aspects of self-awareness may differentially change with recovery and impact outcome. Thus, we examined four self-awareness variables represented in the Dynamic Comprehensive Model of Awareness: metacognitive awareness, anticipatory awareness, error-monitoring, and self-regulation. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 51 publications
1
57
0
Order By: Relevance
“…Therefore, it may be difficult to interpret how our results might generalize to a more diverse population, particularly given that impulsivity has been associated with distinct brain structures in men versus women [Diekhof et al, ]. Furthermore, our use of a self‐report measure in this patient population could be concerning, as there is evidence to suggest that some TBI patients may lack insight or awareness regarding their conditions, potentially weakening the validity of their responses [Kelley et al, ; Robertson and Schmitter‐Edgecombe, ]. As explained above, this concern was addressed by an additional analysis, which made use of available data from a measure that incorporates both patients' and caretakers' reports of the patients' behavioral changes following frontal lobe injury (FrSBe).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be difficult to interpret how our results might generalize to a more diverse population, particularly given that impulsivity has been associated with distinct brain structures in men versus women [Diekhof et al, ]. Furthermore, our use of a self‐report measure in this patient population could be concerning, as there is evidence to suggest that some TBI patients may lack insight or awareness regarding their conditions, potentially weakening the validity of their responses [Kelley et al, ; Robertson and Schmitter‐Edgecombe, ]. As explained above, this concern was addressed by an additional analysis, which made use of available data from a measure that incorporates both patients' and caretakers' reports of the patients' behavioral changes following frontal lobe injury (FrSBe).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also offers practical implications. Impaired awareness can significantly hinder TBI rehabilitation (e.g., Langer & Padrone, ; Lucas & Fleming, ; Medley, Powell, Worthington, Chohan, & Jones, ; Ownsworth & McFarland, ; Robertson & Schmitter‐Edgecombe, ), often due to low compliance levels (e.g., Gasquoine, ). However, direct attempts to increase awareness often lead to negative reactions that can also hinder rehabilitation (e.g., resistance, indifference, agitation; Richardson, McKay, & Ponsford, ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature has demonstrated that self-awareness is vital for successful rehabilitation following acquired brain injury, particularly for several areas included at the Activity and Participation Levels of the World Health Organization's International Classification of Functioning, Disability, and Health, 24 including patient safety, social participation, employability, and community reintegration. 25,26 Hart et al conducted a longitudinal study in the traumatic brain injury population that demonstrates that self-awareness deficits are the most severe during the early stages of recovery, which includes a patient's time in acute rehabilitation. 27 Because stroke survivors also experience impaired insight, this impairment should be considered in the early stages of stroke recovery.…”
Section: Benefits Of Group Treatmentmentioning
confidence: 99%